Analisis faktor-Faktor Yang Mempengaruhi Profitabilitas Pada Perbankan Umum Syariah Di Indonesia Periode 2010-2013 - Fitriyani, Erna; , Eny Setyowati, SE. Msi; , Dr. M. Muhtarom, SH. MH (2016)
This study aimed to test whether a variable Third Party Fund (DPK), Non Performing Financing (NPF), Mudaraba, Murabaha and Musharaka affect the profitability of the Islamic Bank in Indonesia with the object of research that Islamic Banks (BUS) and Sharia (UUS ) in Indonesia using secondary data based on the monthly time series 2010-2013. The analysis technique used is the Model of Multiple Extraordinary Recourse to the significance (α) of 0.05. The results of this study indicate that DPK had a negative and significant impact on the profitability of Bank Syariah, NPF has a negative and significant impact on the profitability of Bank Syariah while Mudaraba, Murabaha and Musharaka positive influence and jointly significant effect on profitability in Islamic Banking in Indonesia in the period 2010-2013.